(untitled) (International Journal of Current Engineering and Technology, 2014)
The insulated wire manufacturing process goes through variety of processes. Quality of wire is primarily determined by the quality formation of PVC paste. For good quality PVC paste formation one of the parameters of concern is the moisture contents in raw PVC and it is necessary to remove complete moisture. For this purpose in Industries an Electrical Oven (EO) is used in which raw PVC filled trays are placed. The paper explicates the design of PID controller and FPD+I controller of PVC moisture-free temperature control. Also simulation based comparative study on the performance of PID controller and FPD+I controller for control of moisture-free PVC temperature is reported. In respect to the performance parameters the FPD+I controller shows better performance than PID controller.